1984
DOI: 10.1126/science.6320371
|View full text |Cite
|
Sign up to set email alerts
|

A Common onc Gene Sequence Transduced by Avian Carcinoma Virus MH2 and by Murine Sarcoma Virus 3611

Abstract: A common cellular sequence was independently transduced by avian carcinoma virus MH2 (v-mht) and murine sarcoma virus (MSV) 3611 (v-raf). Comparison of the nucleotide sequences of v-mht and v-raf revealed a region of homology that extends over 969 nucleotides. The homology between the corresponding amino acids was about 95 percent with only 19 of 323 amino acids being different. With this example, 5 of the 19 known different viral onc genes have been observed in viruses of different taxonomic groups. These dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 19 publications
0
34
0
1
Order By: Relevance
“…Several substitution mutations are observed among vMyc proteins that di er from that of c-Myc (one for CMII, two for OK10, 27 for MH2, three for FTT with two deletions at C-terminus, and ®ve or seven for MC29 depending on the isolate) (Alitalo et al, 1983;Doggett et al, 1989;Hay¯ick et al, 1985;Kan et al, 1984;Reddy et al, 1983;Walther et al, 1985;Watson et al, 1983). Most of the mutations occur in the Nand C-termini of v-Myc, mapping to the domains required for transformation.…”
Section: Mechanisms Of Oncogenic Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several substitution mutations are observed among vMyc proteins that di er from that of c-Myc (one for CMII, two for OK10, 27 for MH2, three for FTT with two deletions at C-terminus, and ®ve or seven for MC29 depending on the isolate) (Alitalo et al, 1983;Doggett et al, 1989;Hay¯ick et al, 1985;Kan et al, 1984;Reddy et al, 1983;Walther et al, 1985;Watson et al, 1983). Most of the mutations occur in the Nand C-termini of v-Myc, mapping to the domains required for transformation.…”
Section: Mechanisms Of Oncogenic Activationmentioning
confidence: 99%
“…Following the advent of recombinant DNA techniques, the viral genome was cloned and the sequence of the v-myc gene was elucidated (Alitalo et al, 1983;Reddy et al, 1983;Watson et al, 1983). Later, the v-myc sequence was found to occur in four other independent retroviral isolates CMII, MH2, OK10 and FTT (Doggett et al, 1989;Hay¯ick et al, 1985;Kan et al, 1984;Walther et al, 1985), which cause di erent neoplastic diseases in their hosts (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…One of the two genes with potential transforming function encoded by MH2 is a 3-kb Agag-mht gene, defined by a p100 protein product (11). A close structural relative of this gene (5,12) is the only transforming gene of murine sarcoma virus MSV 3611 (13).…”
mentioning
confidence: 99%
“…Jansen et al recently reported (9) that the raf oncogene isolated from the murine transforming retrovirus 3611-MSV (20) and the mil (or mht) oncogene isolated from the avian transforming virus MH2 (8,10,11) are homologous genes derived from different species. This observation has been confirmed by direct sequence comparison (12,27). Their deduced amino acid sequences are distantly related to the oncogenes which encode tyrosine-specific kinases as well as others such as erb-B,fms, and mos which apparently do not (14,27).…”
mentioning
confidence: 63%